Application of Neural Network Based Data Security in to LFC of a Two Area Power System - Rathimala, T.; R. Francis; M. Kamarasan (Asian Journal of Electrical Sciences, 2018)
The paper is concentrated with the study of design of a data security system based on neural networks. This data security method added Load-Frequency Control of reheat interconnected two area power systems problems with non-linearity. The neural network control is incorporated to load-frequency control in power systems. Elman Recurrent neural network is involves forecasting controller and system’s output. The system was simulated and the frequency variations in area 1 and area 2 and tie-line power variations for 1% step-load disturbance in area 1 were obtained. The comparison due to frequency variations and tie-line power deviations for the two area interconnected thermal power system. The result data of different keys were taken as test data, encrypted, decrypted and compared with the original data. The results have ensured better its advantages over conventional techniques.